Double defective group modified nitrogen-deficient carbon nitride with bimetallic PtSn as a cocatalyst for efficient photocatalytic hydrogen evolution up to 765 nm. Issue 45 (29th April 2020) - Huang, Shushu; Zhang, Yanxia; Du, Chunfang; Su, Yiguo
Abstract : Cyano- and urea-defective group co-modified nitrogen-deficient carbon nitride with PtSn as a co-catalyst was constructed for stronger light absorption and exceptional photocatalytic hydrogen evolution. Abstract : Cyano- and urea-defective group co-modified nitrogen-deficient carbon nitride with PtSn as a cocatalyst was constructed to optimize the optical and electronic structure as well as the photocatalytic activity. Defective engineering over carbon nitride gave rise to a stronger light absorption in the visible and near-infrared regions, more negative conduction band edge potential and more efficient separation behavior of photogenerated charge carriers. The optimal photocatalyst exhibited a high hydrogen yield of 2.96 mmol g −1 h −1 with an apparent quantum yield of 8.42% at 435 nm. Moreover, the photocatalytic hydrogen generation capability was maintained under illumination up to 765 nm with an apparent quantum yield of 0.076%.